(untitled) (Acta Scientiarum. Biological Sciences, 2014)
The goal of present study was to evaluate the effects of diabetes on quantitative parameters of Leydig cells. Twelve adults Wistar rats were divided in: 1) Diabetic Group (DG), which was induced by a single intraperitoneal injection of streptozotocin (60 mg kg-1 of body weight); and 2) Control Group (CG), which received citrate buffer intraperitoneal. After eight weeks of diabetic induction, the animals were weighted, anesthetized and testicles were removed and routinely processed to paraffin embedded. Body weight (40%) and testicular weight (18%) of diabetic rats were significantly lower than control group. Diabetic rats showed an increase in interstitial compartment but the tubular compartment did not differ. The individual volume of Leydig cells and nuclear diameter were lower in DG. However, the population of these cells was increased. In conclusion, diabetes induced by streptozotocin in adult rats promoted alterations in testicular compartments and changes on volume, nuclear diameter and population of Leydig cells, compromising the testicular function.